Critical Incident Techniques and Reflection in Nursing and Health Professions Education: Systematic Narrative Review. Issue 6 (November 2020) - Steven, Alison; Wilson, Gemma; Turunen, Hannele; Vizcaya-Moreno, M. Flores; Azimirad, Mina; Kakurel, Jayden; Porras, Jari; Tella, Susanna; Pérez-Cañaveras, Rosa; Sasso, Loredana; Aleo, Giuseppe; Myhre, Kristin; et al.
Abstract : Background: The terms critical incident technique and reflection are widely used but often not fully explained, resulting in ambiguity. Purpose: The aims of this review were to map and describe existing approaches to recording or using critical incidents and reflection in nursing and health professions literature over the last decade; identify challenges, facilitating factors, strengths, and weaknesses; and discuss relevance for nursing education. Methods: A systematic narrative review was undertaken. MEDLINE and the Cumulative Index to Nursing and Allied Health Literature were searched using MeSH terms, returning 223 articles (2006-2017). After exclusions, 41 were reviewed. Results: Articles were categorized into 3 areas: descriptions of the development of an original tool or model, critical incidents or reflection on events used as a learning tool, and personal reflections on critical incidents. Conclusions: Benefits have been identified in all areas. More attention is needed to the pedagogy of reflection and the role of educators in reflection. Abstract : Supplemental digital content is available in the text.